2012
DOI: 10.1051/limn/2011057
|View full text |Cite
|
Sign up to set email alerts
|

Bryophyte communities and seston in a karst stream (Jankovac Stream, Papuk Nature Park, Croatia)

Abstract: An investigation into bryophyte communities in karst Jankovac Stream (Papuk Nature Park, Croatia) was carried out once a month from July 2008 to June 2009. Samples were taken from two lotic microhabitats: (i) Jankovac Spring (JS), a hypocrenal habitat with dense bryophyte clusters (90% bottom cover) and (ii) Jankovac Waterfall (JW), with scattered bryophyte clusters (50% bottom cover). At the same time, seston samples were collected during the spring as the source site and after the JW, as the outflow … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
8
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 51 publications
1
8
0
Order By: Relevance
“…Electrical conductivity was high, as expected in streams with limestone substrates that enrich the water with calcium and bicarbonate ions, 38,46 and values were similar in both open and closed canopy areas. Mean pH values were 0.1 higher in the open than closed canopy area.…”
Section: Discussionsupporting
confidence: 71%
See 1 more Smart Citation
“…Electrical conductivity was high, as expected in streams with limestone substrates that enrich the water with calcium and bicarbonate ions, 38,46 and values were similar in both open and closed canopy areas. Mean pH values were 0.1 higher in the open than closed canopy area.…”
Section: Discussionsupporting
confidence: 71%
“…14,28 Unlike previous research, a noticeably higher number of Diptera and Ephemeroptera was found in the present study. 38,46,48 Although the abundance of Baetidae and Chironomidae was very high in natural samples, they were much more abundant in artificial substrates, that is, they colonised artificial substrates very well. A good colonisation pattern in the open canopy area was also seen for Simuliidae individuals.…”
Section: Discussionmentioning
confidence: 99%
“…2007b; Sertic´Peric´et al, 2011). Moreover, in Jankovac Stream, lotic stretches are also covered with bryophyte, which is assumed to contribute to species diversity (Sˇpoljar et al, 2012).…”
Section: Discussionmentioning
confidence: 99%
“…They are based on the collections of Arturo Caballero (first alone) and his daughter Francisca during the 1930s and 1940s when they both worked at the Real Jardín Botánico of Madrid (Álvarez Cobelas, 2020). Fortunately, the present contribution has been carried out in a limestone area of the Peninsula and there are some previous studies in limestone environments with which to compare our results (for example, those of Aboal, 1989Aboal, , 2006Sabater, 1989;Cantonati & Spitale, 2009;Špoljar et al, 2012;Ciorca et al, 2017).…”
Section: Introductionmentioning
confidence: 99%